Conservation status of the African buffalo: a continent-wide assessment - (:unkn) unknown (My University, 2023)
This chapter presents the distribution, abundance patterns and trends of African buffalo in the 38 countries of its distribution area based on recent aerial and ground census data and feedback from field experts. For the period 2001–2021, we collected abundance data from 163 protected areas or complexes of protected areas and presence data from 711 localities. The savanna buffalo population is estimated in 2022 at over 564,000 individuals, after deduction of the 75,000 buffalo under intensive private management in South Africa. Its abundance is roughly equivalent to that estimated 25 years ago (625,000). The subspecies conservation status is highly unbalanced. The Cape buffalo is by far the most abundant, representing 90 per cent of the total estimated population (510,000 individuals). The West and Central subspecies respectively represent 4 and 6 per cent (>20,000 individuals and >34,000 individuals). The conservation status of the Central African savanna buffalo, whose abundance has been nearly halved over the last 25 years, is worrisome, with exception of the steadily increasing populations of Zakouma NP (Chad) and Garamba NP (DRC). Estimating the abundance of forest buffalo is challenging, as is establishing a trend. Our investigations showed that the forest buffalo is still well represented in Central Africa in areas with low human density. The forest buffalo's most important stronghold in Central Africa is probably the Greater TRIDOM/TNS (Tri-National Dja-Odzala-Minkébé / Trinational Sangha), a vast contiguous block of mainly pristine moist forest covering 250,000 km2 and straddling Cameroon, Congo, Gabon and Central African Republic (11 per cent of the Central African forest block). In West Africa, we obtained very little information on the presence of the forest buffalo in the residual forest block, suggesting that the conservation status of the forest buffalo in this region is very worrisome
Keywords: African Research